2022
DOI: 10.3389/fcvm.2022.974802
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and exercise capacity in patients with metabolic syndrome: A cross-sectional study

Abstract: BackgroundMetabolic syndrome is a pre-diabetes condition that is associated with increased cardiovascular morbidity and mortality. We aimed to explore how exercise capacity, cardiac structure, and function were affected in patients with metabolic syndrome.MethodsOutpatients with echocardiography and exercise stress test combined with impedance cardiography (ETT + ICGG) results available from Nov 2018 to Oct 2020 were retrospectively enrolled. Echocardiographic, ETT + ICG profiles, and exercise performance were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Zhou et al 15 found that in patients with multivessel coronary artery disease and acute coronary syndrome, there was no significant difference in LVEF between patients with and without MetS (p = 0.23). In another study, 42 patients with and without MetS also had similar LVEF (p=0.443). The different conclusions in these studies may be because of the different study participants.…”
Section: Discussionmentioning
confidence: 86%
“…Zhou et al 15 found that in patients with multivessel coronary artery disease and acute coronary syndrome, there was no significant difference in LVEF between patients with and without MetS (p = 0.23). In another study, 42 patients with and without MetS also had similar LVEF (p=0.443). The different conclusions in these studies may be because of the different study participants.…”
Section: Discussionmentioning
confidence: 86%